Model Pembelajaran PBL Dalam Meningkatkan Pemahaman Peserta Didik Pada Pembelajaran IPAS Kelas IV SDN 1 Pesu - Rifqi Asiah; Dihan Nanda Hamidah; Isna Rahmawati (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This study aims to determine the effectiveness of the Problem Based Learning (PBL) learning model in increasing the understanding of fourth grade students of SDN 1 Pesu in IPAS subjects. The PBL learning model invites students to learn independently and collaboratively in finding solutions to problems given. In this study using qualitative research methods with data collection techniques through observation and interviews. The results showed that the application of the PBL learning model had improved. The PBL model involves students actively in learning activities. This research contributes to educators in the application of learning strategies that can support academic success and the development of students' understanding. PBL is able to create interactive, relevant, and conducive learning so that it can be an innovative strategy to improve the quality of learning.